Acné: prévalence, perceptions et croyances chez les élèves et étudiants à Ouagadougou, Burkina Faso - Amina Nomtondo Ouedraogo; Sandrine Soutongo Sita Kabre Ouedraogo; Muriel Sidnoma Ouedraogo; Fagnima Traore; Patrice Gilbert Tapsoba; Fatou Barro-Traore; Adama Traore; Pascal Niamba (Our Dermatology Online, 2017)
Introduction: Acne, is a common disease. Its prevalence is 80% among adolescents in the world and 57,1% in Ouagadougou in 2001 among school pupils. The medical literature is provided on the epidemiological, clinical and therapeutic aspects of acne, and less on perceptions and knowledge of acne patients of their disease. The objective of this study was to evaluate the prevalence, knowledge, beliefs on acne, among pupils and students in Ouagadougou. Patients and Methods: We conducted a cross-sectional study from June to July 2014 in the University of Ouagadougou and in 4 secondary schools in Ouagadougou. Results: We surveyed 425personnes including 40.6% of girls and 59.4% boys. The prevalence of acne was 54.8%. The mean age was 19.53 years, with extremes ranging from 13 to 30 years. Among the etiologies, food was cited by 40.05%, 25.43% puberty, cosmetics 14.03% 3.21% hormones, stress 2.33%, 0.87% seborrhea. Among the foods concerned, peanuts were cited by 37.96%, 21.22% mayonnaise, butter, 21.52%, 8.07% sweets and chocolate 9,41%. oil was incriminated by 72.6% and sugar 5.5%. Among the contributing factors, 19.70% cited tobacco, 19% no sexual relationship. Among the 192 non acne patients, 17% link acne to poor hygiene, 80% would be embarrassed to have a partner acne, 74.40% of non-acne believed that acne altered self-image. For treating acne 26.11% think that acne is incurable. Cosmetic can care acné according to 37,90% and 6,30% believed that natural products are sufficient. Only 15.02% have resorted to a dermatologist. Conclusion: Pupils and students have bad knowledge on acne and bad perception on those who have the disease.